Thông báo về kế hoạch tổ chức các Hội nghị của Hội Tim mạch học Việt Nam năm 2016 - Nguyễn Lân Việt (Tạp chí Tim mạch học Việt Nam, 2016)
Thông báo về kế hoạch tổ chức các Hội nghị của Hội Tim mạch học Việt Nam năm 2016